Firm’s Resilience Before and During Covid-19 Pandemic - Sriani, Dewi; Wahyu Subroto, Radityo (Journal of Trends Economics and Accounting Research, 2024)
This research aims to investigate the company’s resilience before and during Covid-19 pandemic. The study examines the differences between firm performance and the average performance using Return on Assets (ROA), Total Asset Turnover (TATO), and current ratio (CR) before and during Covid-19 pandemic. This study uses sample from non-cyclical consumer industries listed on the Indonesian Stock Exchange (BEI) for the period 2017-2022 with 258 firm years observation. The data is analyzed with SPSS using paired t-test sample with Wilcoxson Test. The results show that there is a significant performance difference as measured by ROA and TATO before and during Covid-19. The mean ROA value was 8% before and 5.54% during the covid-19 epidemic, respectively. TATO levels were 0.99 and 0.87 correspondingly before and during the covid-19 epidemic. The current ratio, however, does not alter between the two periods. The mean value of current ratio was 2,46 and 2,49 respectively before and during covid-19. The findings also revealed that there is no difference in non-cyclical industries' average performance (ROA, CR, and TATO) before and after the Covid-19 pandemic.